Cultivated Pastures Affect Nutrient Intake and Feeding Behavior of Sheep - Emerenciano Neto, J. V.; Difante, G. S.; Medeiros, H. R.; Aguiar, E. M.; Fernandes, L. S.; Trindade, T. F. M.; Bezerra, M. G. S.; Oliveira, H. C. B.; Galvão, R. C. P. (Tropical Animal Science Journal, 2020)
Cultivated pastures may increase the meat production of sheep, but it is necessary to understand the plant-animal relationships in a pastoral environment. This study aimed to assess the effect of forage cultivars on the intake and feeding behavior of sheep. Four treatments were evaluated, consisted of the cultivars Panicum maximum cvs. Aruana and Massai and Brachiaria brizantha cvs. Marandu and Piatã. Twenty-four sheep, male of the Santa Inês genotype, were used with six replications per treatment. Daily forage and nutrient intakes were evaluated in addition to time in grazing, rumination, and leisure activities. The animals in the pasture of Aruana grass demanded the most extended times of grazing and rumination (p